Schizophrenia and cell senescence candidate genes screening, machine learning, diagnostic models, and drug prediction - Feng, Yu; Shen, Jing; He, Jin; Lu, Minyan (Frontiers in Psychiatry, 2023)
Schizophrenia (SC) is one of the most common psychiatric diseases. Its potential pathogenic genes and effective treatment methods are still unclear. Cell senescence has been confirmed in mental diseases. Therefore, the aims of this study were to identify candidate genes based on cell senescence that can affect the diagnosis and treatment of schizophrenia.